Portlandia. Season eight [videorecording (DVD)] - Brownstein, Carrie, 1974-; Brownstein, Carrie, 1974-; Brownstein, Carrie, 1974-; Wagner, Graham; Armisen, Fred, 1966-; Armisen, Fred, 1966-; MacLachlan, Kyle, 1959- ([publisher not identified], 2018)
A series of short comedy sketches centered around the fictitious town of Portlandia and 1990s pop culture.